Combined Cell Surface Display of β‐d‐Glucosidase (BGL), Maltose Transporter (MAL11), and Overexpression of Cytosolic Xylose Reductase (XR) in Saccharomyces cerevisiae Enhance Cellobiose/Xylose Coutilization for Xylitol Bioproduction from Lignocellulosic Biomass. Issue 9 (13th August 2019) - Guirimand, Gregory G. Y.; Bamba, Takahiro; Matsuda, Mami; Inokuma, Kentaro; Morita, Kenta; Kitada, Yuki; Kobayashi, Yuma; Yukawa, Takahiro; Sasaki, Kengo; Ogino, Chiaki; Hasunuma, Tomohisa; Kondo, Akihiko
Abstract : Xylitol is a highly valuable commodity chemical used extensively in the food and pharmaceutical industries. The production of xylitol fromd ‐xylose involves a costly and polluting catalytic hydrogenation process. Biotechnological production from lignocellulosic biomass by micro‐organisms like yeasts is a promising option. In this study, xylitol is produced from lignocellulosic biomass by a recombinant strain of Saccharomyces cerevisiae ( S. cerevisiae ) (YPH499‐ Ss XR‐ Aa BGL) expressing cytosolic xylose reductase ( Scheffersomyces stipitis xylose reductase [ Ss XR]), along with a β‐d ‐glucosidase ( Aspergillus aculeatus β‐glucosidase 1 [ Aa BGL]) displayed on the cell surface. The simultaneous cofermentation of cellobiose/xylose by this strain leads to an ≈2.5‐fold increase in Yxylitol/xylose (=0.54) compared to the use of a glucose/xylose mixture as a substrate. Further improvement in the xylose uptake by the cell is achieved by a broad evaluation of several homologous and heterologous transporters. Homologous maltose transporter ( Sc MAL11) shows the best performance in xylose transport and is used to generate the strain YPH499‐XR‐ Sc MAL11‐BGL with a significantly improved xylitol production capacity from cellobiose/xylose coutilization. This report constitutes a promising proof of concept to further scale up the biorefinery industrial production of xylitol from lignocellulose by combining cell surface and metabolic engineering in S. cerevisiae . Abstract : Xylitol is produced from lignocellulosic biomass (rice straw hydrolysate; kraft pulp residues) by a recombinant strain of Saccharomyces cerevisiae ( S. cerevisiae ) (YPH499‐ Ss XR‐ Sc MAL11‐AaBGL). This strain is expressing cytosolic xylose reductase ( Scheffersomyces stipitis xylose reductase [ Ss XR]), along with the homologous maltose transporter ( Sc MAL11) and β‐d‐glucosidase ( Aspergillus aculeatus β‐glucosidase 1 [AaBGL]) displayed on the cell surface, to efficiently co‐utilize cellobiose and xylose to produce xylitol.